What do we know about mental health of medical personnel? A systematic review - Aprilia, Eka Dian; Adam, Muhammad; Zulkarnain, Zulkarnain; Mawarpury, Marty (Utan Kayu Publishing, 2024)
Medical personnel is a profession with a high workload. High work demands can lead to a decline in physical and emotional health. An in-depth understanding of the impact of workload on health, especially mental health, is crucial to implementing measures for their well-being. This literature review aims to gather and compare available information to produce an apparent picture of the mental health of medical personnel and influencing factors. A comprehensive search was conducted utilizing a variety of electronic databases, including Scopus, Science Direct, Springer Link, ProQuest, EBSCO, MED-LINE, and Google Scholar. The literature search focused on papers assessed with the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) methodology. We identified 16 studies that reported the criteria for in-depth analysis. The study concluded that overburdened medical personnel are prone to burnout, which in turn has the potential to lead to mental health problems. Common disorders are burnout, depression, anxiety, and abnormal stress. Further research sourced from internal individuals needs to be done so that it is expected to be more robust and consistent, considering that medical personnel are very likely to work in more than one institution during the process.